(1) (15 x 3) ÷ 5x 8-2+ 6 (8-2)
Answers
Answered by
2
Answer
asdfghjkl
asdfghjkl
Attachments:
![](https://hi-static.z-dn.net/files/da0/4bda95a92fa4c091e9d3773fae8a7db0.jpg)
Answered by
1
Step-by-step explanation:
(15 x 3) ÷ 5x 8-2+ 6 (8-2)
= 45 ÷ 5 × 6 + 6 × 6
= 9 × 6 + 6 × 6
= 54 + 36
= 90
Similar questions
Chemistry,
2 months ago
English,
2 months ago
English,
2 months ago
Math,
4 months ago
English,
4 months ago
Social Sciences,
11 months ago
Physics,
11 months ago
Social Sciences,
11 months ago